The Development of Web-Based E-Modules in Class XI Marching Materials on SMA Negeri 11 Pinrang - Rusli Rusli; Ahmad Talib; Hastuty Musa; Abdul Rahman; Nur Ikhsan Ismail (PT ARRUS Intelektual Indonesia, 2023)
This study aimed to develop and produce valid, practical, and effective web-based e-module products to help students understand the sequencing material for the Eleventh Grade at Senior High School 11 Pinrang. This research was conducted at Senior High School 11 Pinrang. The research method refers to Thiagarajan 4D development model, which consists of 3 stages: define, design, develop, and disseminate. The development research began with the defining stage, which consisted of defining a problem based on students, assignments, materials, and learning objectives. The design stages include compiling, designing, and determining formats. The development stage involves validation of material and media experts, followed by testing. Firthermore, the dissemination stage was limited to Senior High School 11 Pinrang in different classes. Research instruments used in this study included validation sheets by material experts and media experts to measure validity, student response questionnaires to measure practicality, and learning achievement test questions to measure effectiveness. The trial was performed on class XI MIPA 2 students at Senior High School 11 Pinrang. The results showed that the web-based e-module on class XI lineup material that was developed was valid with a score of 3.72 in terms of material and a score of 3.70 in terms of media which was included in valid and unrevised criteria, practically by obtaining a very positive response from students and teacher responses with a score of 3.56 for student responses and a score of 3.38 for teacher responses, and effective based on student learning outcomes tests with an effectiveness score on the percentage of completeness of the trial subjects of 88.46%.